On loss compensation, amplification and lasing in metallic metamaterials. (3rd January 2019) - Droulias, Sotiris; Koschny, Thomas; Kafesaki, Maria; Soukoulis, Costas M
The design of metamaterials, which are artificial materials that can offer unique electromagnetic properties, is based on the excitation of strong resonant modes. Unfortunately, material absorption—mainly due to their metallic parts—can damp their resonances and hinder their operation. Incorporating a gain material can balance these losses, but this must be performed properly, as a reduced or even eliminated absorption does not guarantee loss compensation. Here we examine the possible regimes of interaction of a gain material with a passive metamaterial and show that background amplification and loss compensation are two extreme opposites, both of which can lead to lasing.